The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 2nd ACM/IEEE-CS Joint Conference on Digital Libraries 2002
DOI: 10.1145/544220.544262
|View full text |Cite
|
Sign up to set email alerts
|

Towards an electronic variorum edition of Cervantes' Don Quixote :

Abstract: The Cervantes Project is creating an Electronic Variorum Edition (EVE) of Cervantes' well-known Don Quixote de la Mancha, published beginning in 1605. In this paper, we report on visualizations of features of a text collection that help us validate our text transcriptions and understand the relationships among the different printings of an edition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Our examination of the visualization pointed out examples of transcription errors (due to unclear patches in the original microfilms), one "unexpected" action taken by the collation algorithm (represented by the unusually long length of one of the variances), and differences of the form identified by others previously (including those in the first two pages). See [11] for further explanation of this display. Our static visualization only depicted the results in the screen, but did not provide further information such as the content of the variant, its length in characters, and the offset in the text; nor does allow interaction.…”
Section: Visualizations For Validating the Results Of The Collationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our examination of the visualization pointed out examples of transcription errors (due to unclear patches in the original microfilms), one "unexpected" action taken by the collation algorithm (represented by the unusually long length of one of the variances), and differences of the form identified by others previously (including those in the first two pages). See [11] for further explanation of this display. Our static visualization only depicted the results in the screen, but did not provide further information such as the content of the variant, its length in characters, and the offset in the text; nor does allow interaction.…”
Section: Visualizations For Validating the Results Of The Collationmentioning
confidence: 99%
“…Furthermore, we recognize a practical need in our project to validate the accuracy of the transcriptions of the texts, since those are created manually from an electronic template. Previously, we have described briefly [11] our use of visualizations to depict the variants, and its utility in presenting anomalies that require further investigation. In this paper, we report further on our application of visualizations in detecting patterns of interest within collections of copies or editions of a text.…”
Section: Introductionmentioning
confidence: 99%
“…We are in the process of creating an Electronic Variorum Edition (EVE) of Miguel de Cervantes y Saavedra's (Spain, 1547-1616) Don Quixote [4,5,6]. The EVE will be included in the Cervantes Digital Library (CDL), part of the ongoing Cervantes Project [13].…”
Section: Introductionmentioning
confidence: 99%
“…The Web has clearly allowed new intellectual communities to form, and many intellectual resources formerly available only onsite in special collections are now receiving substantial electronic use (e.g. [20][21][22][23]). The 315 million page-accesses we have tracked since 1996 are a useful diachronic dataset that we are beginning to use to track the evolution of user behavior, while the thousands of email messages to webmaster@perseus.tufts.edu trace the reactions of a patron group (albeit a self-selecting one).…”
Section: Audiencesmentioning
confidence: 99%
“…The efforts of the Perseus Project are based on a strong and somewhat polemical premise: namely, that digital libraries promise new methods by means of which new audiences can ask new questions about new ideas they would never otherwise have been able to explore. While we are based in a university and we are products of US higher education, we see the peer-to-peer interactions between professional colleagues [1][2][3] and indeed the formal instruction of 18-22 year old students [4,5] as instruments for a broader purpose. In one recent survey of 1,500 people, "two fifths … reported that they pursue a hobby or collection related to the past, and they spoke of those pursuits with words like 'love' and 'passion'" [6].…”
Section: Introductionmentioning
confidence: 99%